Collective Protest and Expressive Action Among University Students in Hong Kong: Associations Between Offline and Online Forms of Political Participation - Reichert, Frank (Frontiers in Political Science, 2021)
Youth have often been described as politically apathetic or disengaged, particularly with respect to more conventional forms of participation. However, they tend to prefer non-institutionalized modes of political action and they may express themselves on the Internet. Young people have also been recognized as having a “latent preparedness” to get politically active when needed. This paper reports forms of offline and online participation adopted by young adults in Hong Kong who were surveyed shortly before the anti-extradition bill social movement of 2019 and 1 year later. The results tentatively suggest that young adults may not be very active in politics when they do not perceive the need to bring about change. However, they are involved in expressive activities and on the Internet more broadly, and ready to turn their latent participation into concrete political participation when they are dissatisfied with government actions and believe it is their responsibility to act against laws perceived to be unjust. Cross-sectional and cross-lagged panel analyses show that youth’s participation in offline political activities is associated with their online participation. Positive effects of past experiences in each mode on participation in offline and online political activities show the mobilizing potential of social media and provide support for the reinforcement hypothesis, though previous participation in offline activities appears as a better predictor of political participation when compared with prior participation on the Internet.